2007
DOI: 10.3390/s7123416
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-based Flood Modeling Using TRMM-based Rainfall Products

Abstract: Increasingly available and a virtually uninterrupted supply of satellite-estimated rainfall data is gradually becoming a cost-effective source of input for flood prediction under a variety of circumstances. However, most real-time and quasi-global satellite rainfall products are currently available at spatial scales ranging from 0.25° to 0.50° and hence, are considered somewhat coarse for dynamic hydrologic modeling of basin-scale flood events. This study assesses the question: what are the hydrologic implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 26 publications
2
56
0
4
Order By: Relevance
“…For the GSMaP products, which are available in near real time (about 4 hours after observation) via the Internet (Kachi et al 2011), analysis data such as the JMA global analysis or forecasting data should be used instead of the reanalysis data used here. Despite these remaining issues, this study shows a remarkable advance in high-resolution satellite rainfall products and in the possibility of their application to flood and landslide analysis/prediction because signals of heavy rainfall are vital for these applications (Harris et al 2007;Hong et al 2007). The revised GSMaP algorithm succeeds in detecting heavy orographic rainfall continuously in the sense of time and space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the GSMaP products, which are available in near real time (about 4 hours after observation) via the Internet (Kachi et al 2011), analysis data such as the JMA global analysis or forecasting data should be used instead of the reanalysis data used here. Despite these remaining issues, this study shows a remarkable advance in high-resolution satellite rainfall products and in the possibility of their application to flood and landslide analysis/prediction because signals of heavy rainfall are vital for these applications (Harris et al 2007;Hong et al 2007). The revised GSMaP algorithm succeeds in detecting heavy orographic rainfall continuously in the sense of time and space.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Chen et al (2013) showed that the TMPA 3B42, which is adjusted by gauged measurements, presented less heavy rainfall than the TMPA 3B42RT, probably because of the process of rescaling the TMPA 3B42RT to the monthly rain gauge data. As signals of heavy rainfall are indispensable for flood and landslide analysis/prediction applications (Harris et al 2007;Hong et al 2007), it is a remarkable advance for these applications that the revised GSMaP algorithm succeeds in detecting heavy orographic rainfall continuously in the sense of time and space, while the present algorithms fail. The results indicate that the revised GSMaP algorithm is quite effective for the Taiwan case if the horizontal length scale for averaging the elevation data is appropriate for calculating w oro and if the thresholds in Eq.…”
Section: Fig 5 Correlation Coefficients Between Pr 2a25 Near-surfacmentioning
confidence: 99%
“…For the detailed methodology of the ModClark, readers can see references [55][56][57]. Also, many previous studies have used the ModClark for various hydrologic applications [58][59][60][61][62][63][64]. In most of the studies cited above, the CN method was used with the ModClark approach.…”
Section: Application Instancementioning
confidence: 99%
“…One such satellite rainfall product, the National Aeronautics and Space Administration (NASA) Tropical Rainfall Measuring Mission (TRMM) has been used extensively and provides quasi global (50 o S-50 o N) precipitation analyses at 3-hourly, 0.25 o latitudelongitude resolution, with all satellite estimates calibrated or adjusted to the information from the TRMM satellite itself, which carries both a radar and passive microwave sensor [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that 69 villages in 13 sub-districts in Rokan Hulu regency was inundated by the flood, 18 people were killed, 17,816 houses were damaged, and 53,725 people were evacuated [13]. (1) to (5). In the process of river routing, the Kinematic Wave Model is employed.…”
Section: Introductionmentioning
confidence: 99%